2020
DOI: 10.1007/978-3-030-40348-5_6
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Chemical Reduction of Chlorinated Organic Compounds

Abstract: Chlorinated organic compounds (COCs) are common anthropogenic contaminants of soil and groundwater. COCs were industrially produced for different applications, such as dry cleaning, degreasing, or as pesticides. The presence of COCs in the environment is a major concern because of their toxicity and persistence.The most widely used method for their remediation is the conventional pump-and-treat system. However, this technology can hardly achieve a complete remediation because of geological characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 536 publications
(673 reference statements)
0
4
0
Order By: Relevance
“…In a more recent study, Tamang and co-workers have reported that colloidal CsPbBr 3 QDs provide efficient visible-light photocatalysts to trigger organic transformations, namely, synthesis of a broad range of azaheterocycles, via oxidative aromatization . Conversely, in situ chemical reduction of chlorinated hydrocarbons using iron-based nanoparticles has been actively pursued, as these are common groundwater and soil pollutants. , Cyclic voltammetry was employed to investigate the electrochemical degradation routes of alkyl chloride molecules in either aqueous or organic solutions . These studies have shown that each medium produces different reaction pathways involving different intermediates .…”
Section: Resultsmentioning
confidence: 99%
“…In a more recent study, Tamang and co-workers have reported that colloidal CsPbBr 3 QDs provide efficient visible-light photocatalysts to trigger organic transformations, namely, synthesis of a broad range of azaheterocycles, via oxidative aromatization . Conversely, in situ chemical reduction of chlorinated hydrocarbons using iron-based nanoparticles has been actively pursued, as these are common groundwater and soil pollutants. , Cyclic voltammetry was employed to investigate the electrochemical degradation routes of alkyl chloride molecules in either aqueous or organic solutions . These studies have shown that each medium produces different reaction pathways involving different intermediates .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the research aiming to improve the purification technologies for removing such dangerous chemicals from liquid waste and wastewater is of high demand. Various methods have been proposed for the removal of COCs from water, including catalytic oxidation [ 5 ]; biodegradation [ 6 ]; advanced oxidation processes, such as photocatalytic destruction [ 7 ] or electrochemical degradation [ 8 ]; reductive dechlorination [ 9 ]; as well as non-destructive methods, such as adsorption [ 10 , 11 , 12 ]. Each of these methods has its advantages and limitations [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The two major problems associated with aged CAHs-contaminated sites are the secondary source management and the containment and remediation of the contamination plume. Secondary source refers to the presence of the solvent in a separate phase, primarily accumulated in the low-permeability layers of the aquifer (clay lens), which work as a source of long-term contaminants [ 5 ]. On the other hand, contamination plume refers to prolonged contamination in the same direction of water flow due to the slow and steady release of secondary sources.…”
Section: Introductionmentioning
confidence: 99%